2017
DOI: 10.1111/tpj.13399
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of rice essential genes by characterizing a CRISPR‐edited mutation of closely related rice MAP kinase genes

Abstract: SUMMARYThe clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 nuclease (Cas9) system depends on a guide RNA (gRNA) to specify its target. By efficiently co-expressing multiple gRNAs that target different genomic sites, the polycistronic tRNA-gRNA gene (PTG) strategy enables multiplex gene editing in the family of closely related mitogen-activated protein kinase (MPK) genes in Oryza sativa (rice). In this study, we identified MPK1 and MPK6 (Arabidopsis AtMPK6 and AtMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Multiplex PTG/Cas9 systems can help with multigene family analysis, as reported for the closely related mitogen-activated protein kinase MPK1 and MPK6 in rice (Minkenberg et al, 2017). 67% of all lines were double mutants for MPK genes with a high frequency of biallelic mutations on multiple target sites.…”
Section: Multiplex Genome Editing: When Does It Become Useful?mentioning
confidence: 99%
“…Multiplex PTG/Cas9 systems can help with multigene family analysis, as reported for the closely related mitogen-activated protein kinase MPK1 and MPK6 in rice (Minkenberg et al, 2017). 67% of all lines were double mutants for MPK genes with a high frequency of biallelic mutations on multiple target sites.…”
Section: Multiplex Genome Editing: When Does It Become Useful?mentioning
confidence: 99%
“…The start and end sites of the tRNA in the tandemly arrayed tRNA‐sgRNA transcripts are precisely recognized and cleaved by endogenous RNases (RNase P and RNase Z in plants) to simultaneously produce multiple functional sgRNAs (Xie et al ., ). Additionally, the tRNA gene contains internal promoter elements, suggesting that it may work as a potential transcriptional enhancer, as verified in a recent study involving rice, which showed that the relative expression level of the sgRNA in the PTG/Cas9 system is higher than in the CRISPR/Cas9 system (Minkenberg et al ., ; Xie et al ., ). Compared to the traditional CRISPR/Cas9 system, the PTG/Cas9 system is simpler and more efficient for multiplex targeted genome modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of proxies of gene editing in the T2 progenies could 117 significantly reduce the time and effort invested in identifying CRISPR-mutagenized 118 plants. 119 CRISPR/Cas9 can simultaneously edit multiple loci (co-editing) at high frequency in the 120 somatic tissues of T1 Arabidopsis and rice plants (Ma et al 2015;Yan et al 2016;121 Zhang et al 2016;Minkenberg et al 2017). Hence, we hypothesized that we could take 122 advantage of this high co-editing frequency to aid in the selection of CRISPR-123 mutagenized plants.…”
Section: Introduction 46mentioning
confidence: 99%